Attitudes of hospital patients regarding removal of processed and unprocessed red meats from menus to support sustainable healthcare targets: A single‐centre survey - Melissa Truman; Laura‐Jane Smith; Shireen Kassam (Wiley, 2023)
Abstract Background The production and consumption of red and processed meat negatively impacts individual and planetary health. The 2021 Lancet countdown on health and climate change report stated that 842,000 deaths annually are due to excess red meat consumption, whilst its production is responsible for more than 50% of food‐related greenhouse gas emissions. As part of the National Health Service's net‐zero emissions strategy, King's College Hospital has committed to transitioning to a plant‐based food environment and removing processed red meat from menus. Aims To ascertain patients' attitudes to the removal of processed and unprocessed red meat from menus Material and methods We conducted a survey of 118 patients using in‐person interviews. Results Most patients did not consider serving processed red meat (74%) or unprocessed red meat (66.1%) important to them and most patients (77.9%) were neutral or supportive of removing processed red meat from menus to reduce the risk of cancer. Most patients (67%) were also supportive of removing unprocessed red meat from menus to combat climate change. The majority would choose chicken or fish in place of red meat. Conclusion These data show that patients would support the removal of red meat from hospital menus, but more education is required to support patients to select plant‐based options.